Research on Mapping the Knowledge Domain of Digital Curation——A Bibliometric Study of Web of Science(1990-2016) - Yu Chenlin (Zhishi guanli luntan, 2017)
[Purpose/significance] Digital Curation (DC) is an important part of research data management in e-Science environment. By systematically combing the research progress and proposing some issues worthy of further studying, this paper aims to provide a basis and reference for national research data management research. [Method/process] Documents relevant to data curation were retrieved from Web of Science database. With CiteSpace Ⅲ software based on the document co-citation analysis method, this paper drew the knowledge map of international digital curation. In terms of research-based subject distribution, research institutions, researchers and knowledge of the four dimensions, the related contents were analyzed and summarized with the content analysis method. [Result/conclusion] International digital curation research began in 2000. Now it has entered a mature period, with a specific research disciplines, institutions and groups. The research’s knowledge base is data description, integration and association, data maintenance in the scientific research process and value-added activities, data management stakeholders and service innovation models of library services.